Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

answer please.......​

Answer Please class=

Sagot :

HoOsKy

Answer:

7.2

Step-by-step explanation:

[tex]A^{2} + B^{2} =C^{2} \\6^{2} +4^{2} =C^{2}\\6^{2} = 36\\4^{2} =16\\36+16= 52\\\sqrt{52} = 7.2[/tex]

Given:

Base length of triangle = 6 units

Height of triangle = 4 units

To find:

Length of hypotenuse of triangle

Steps:

Pythagoras theorem states that,

A² + B² = C²

Here A and B represent height and length of triangle, and C represents the hypotenuse of the triangle.

So, implementing our measurements we get

A = 6 units

B = 4 units

C =  C units

    A² + B² = C²

     6² + 4² = C²

    36 + 16 = C²

           52 = C²

         [tex]\sqrt{52} = \sqrt{C^{2} }[/tex]

[tex]\sqrt{2 * 2*13} = C[/tex]

       [tex]2\sqrt{13} = C[/tex]

            [tex]C = 2\sqrt{13}[/tex]

         [tex]\sqrt{13} = 3.6[/tex]

            [tex]C = 2 * 3.6[/tex]

            [tex]C = 7.2[/tex] units

Therefore, the length of the Hypotenuse of the triangle or the length of C is 7.2 units

HAPPY TO HELP :)

If you need any help feel free to ask

Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.